Metric Based Automatic Quality Analysis of Object Oriented Systems - Jatain, A (International Journal of Computer Sciences and Engineering, 2025)
Today most of the languages support objects oriented architecture to develop an organized software system and customer base for these system is increasing because incentives in object oriented paradigm is huge. At the same time, drawback is that object oriented systems are complex and difficult to understand. So quality of these system must be monitored and maintained which require lots of money, time and efforts. In software community when prediction is made based on metrics, software quality is one of the most discussed term. Software quality can be estimated by analyzing the key quality attributes of the software system. The objective of this paper is to define a metric suite and designing of automatic tool to evaluate the object oriented software system under complexity analysis in order to analyze the software criticality. Methodology: This paper focusses on automatic quality analysis of object oriented system. For this different metrics and metric suites are analyzed and a tool is developed in .net environment that accept software program as input and perform a metric based analysis. To validate the tool a case study (LMS) is considered as input.